Mesenchymal Stromal Cells Within Fibrin Gel Stimulate Healing of Full-Thickness Wounds in Mice - Tykhvynska, Olga A.; Rogulska, Olena Yu.; Petrenko, Yuriy A. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):171.